2019
DOI: 10.4236/ojepi.2019.91001
|View full text |Cite
|
Sign up to set email alerts
|

From Social Determinants of Health Actions to Fight against the Lassa Virus Hemorrhagic Fever Epidemic in Tchaourou Commune in Benin, 2018

Abstract: Background: Lassa Hemorrhagic Fever (LHF) is endemo-epidemic in West Africa with seasonal outbreaks raising a major public health issue. Nigeria borders Benin by the Tchaourou Commune. Since 2016, Tchaourou commune has been affected every year by this epidemic. Objective: To study how an action on the health social determinants can contribute to ending this epidemic in Tchaourou commune, Benin. Methods: This cross-sectional study was conducted in Tchaourou commune. All of the cases of LHF occurring in 2016-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…CP has been documented in improving community hygiene practices in the prevention of Lassa fever and other infectious diseases. 13 However, paucity of knowledge yet exists on the mechanism behind CP in the context of the COVID-19 vaccine. Given that acceptance of the COVID-19 vaccine is a major requirement towards attaining herd immunity against SARS-CoV-2, 14 this perspective aimed to describe how CP could be adopted to promote COVID-19 vaccination acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…CP has been documented in improving community hygiene practices in the prevention of Lassa fever and other infectious diseases. 13 However, paucity of knowledge yet exists on the mechanism behind CP in the context of the COVID-19 vaccine. Given that acceptance of the COVID-19 vaccine is a major requirement towards attaining herd immunity against SARS-CoV-2, 14 this perspective aimed to describe how CP could be adopted to promote COVID-19 vaccination acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…The study pointed evidence to engaging community members in risk communication and stakeholders mobilization. Stakeholders were saddled with the responsibility of discouraging rats' hunting and consumption, bush burningh, and banning cultural norms of cutting parts of a deceased body for prayers [18] . Patassi et al (2017) conducted a case report describing the response to the first two cases of LF infection in Togo in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review across LF-endemic countries presented evidence about the importance of community participation as a component of the disease outbreak response. Community participation is aimed not only at reducing the magnitude of the outbreak, but also at preventing future outbreaks [18] . Despite the lack of sufficient studies to be included in this review, community members were found to play the greatest role in community mobilization towards the prevention and control of LF infection [8,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations